The effectiveness of innovation policy and the moderating role of market competition: Evidence from Latin American firms - Jose Miguel Benavente; Pluvia Zuniga (United Nations University (UNU), Maastricht Economic and Social Research Institute on Innovation and Technology (UNU-MERIT), 2021)
The objective of this paper is to evaluate whether market competition matters for the effectiveness of innovation policies. Using data for Chilean and Peruvian manufacturing firms, we implement propensity matching techniques combined with differences-in-differences estimation to evaluate the impact of innovation subsidies on the post-treatment innovation investment effort of firms and test whether such impact differs according to the intensity of competition. We corroborate the existence of "crowding-in" effects in beneficiaries when compared to a control group of untreated firms. The subsidy impact is found either only significant in highly competitive sectors or larger in more competition-intensive industries -compared to low competition ones. Thus, we confirm that market competition plays a moderating role in the effectiveness of innovation policies to stimulate firm innovation investment. The results are robust to different matching and estimation methods. Our results therefore suggest that market contexts should be considered in the design of innovation policies.
Keywords: O38; O31; R38; H71; 330; Innovation Subsidies; Innovation Policy; Market Competition Latin American firms